Home bias and expected returns: A structural approach. (June 2022) - Wallmeier, Martin; Iseli, Christoph
Highlights: We propose a new method to measure the impact of the home bias on expected returns. The overall home bias has decreased over time but is still substantial. Although the home bias is strong, the home premium is almost negligible. One reason is that country returns are highly correlated. Another reason is that the home bias is similarly strong in different countries. Abstract: We study the effect of the home bias on international asset pricing by extending the core-satellite approach of active asset allocation to an equilibrium analysis. In this framework, investors combine a common core portfolio with an active investment in their home asset. In equilibrium, the core portfolio will deviate from the global market portfolio in characteristic ways, which we exploit to propose a new test of the home premium in expected returns. Unlike previous findings, our evidence suggests that the premium is almost negligible even though the home bias is substantial. This result is mainly driven by the generally high correlation of index returns and the distribution of the relative level of the home bias across countries.